CONTEMPORARY LINGUISTIC TRENDS AND THEIR APPLICATIONS IN ARABIC LANGUAGE TEACHING - Althaf Javid H. Aziz; Dewy Sartika; Hayatun Nissa; Dika Syam El-Fathony; Fachrul Ghazi (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT Modern linguistic schools, such as structuralism, transformational-generative linguistics, functionalism, and sociolinguistics, have made significant contributions to the development of language theory and teaching practices. In Arabic language learning, understanding these linguistic approaches serves as a strategic foundation for designing curricula, instructional methods, and assessment systems that are more effective and responsive to learners’ needs. This study aims to identify the major schools of modern linguistics, analyze their fundamental characteristics, and examine their relevance to Arabic language teaching. The study employs a library research method with a descriptive-analytical approach through the review of various primary and secondary sources in both theoretical and applied linguistics. The findings indicate that each linguistic school offers distinct perspectives for Arabic language learning, ranging from strengthening structural and grammatical aspects to developing communicative competence and incorporating social and cultural contexts into the learning process. The study further reveals that no single linguistic approach can fully address the diverse needs of Arabic language instruction. Therefore, an integrative approach that combines the strengths of various linguistic schools is necessary to accommodate different learning objectives, instructional materials, and learner characteristics. In conclusion, the integrated application of modern linguistic approaches can enhance the effectiveness of Arabic language teaching while fostering learners’ linguistic and communicative competence. ABSTRAK Aliran linguistik modern seperti strukturalisme, transformasional-generatif, fungsionalisme, dan sosiolinguistik telah memberikan kontribusi penting terhadap perkembangan teori dan praktik pengajaran bahasa. Dalam pembelajaran bahasa Arab, pemahaman terhadap berbagai aliran linguistik menjadi landasan strategis untuk merancang kurikulum, metode pembelajaran, dan sistem evaluasi yang lebih efektif serta sesuai dengan kebutuhan peserta didik. Penelitian ini bertujuan untuk mengidentifikasi aliran-aliran linguistik modern utama, menganalisis karakteristik dasarnya, serta mengkaji relevansinya dalam pembelajaran bahasa Arab. Metode yang digunakan adalah kajian pustaka (library research) dengan pendekatan deskriptif-analitis melalui penelaahan berbagai sumber primer dan sekunder dalam bidang linguistik teoretis maupun terapan. Hasil penelitian menunjukkan bahwa setiap aliran linguistik menawarkan perspektif yang berbeda dalam pembelajaran bahasa Arab, mulai dari penguatan aspek struktural dan gramatikal, pengembangan kompetensi komunikatif, hingga pemanfaatan konteks sosial dan budaya sebagai bagian dari proses pembelajaran. Temuan ini mengindikasikan bahwa tidak ada satu aliran yang sepenuhnya mampu menjawab seluruh kebutuhan pembelajaran bahasa Arab, sehingga diperlukan pendekatan integratif yang mengombinasikan keunggulan berbagai aliran linguistik sesuai dengan tujuan, materi, dan karakteristik peserta didik. Dengan demikian, penerapan pendekatan linguistik modern secara terpadu dapat meningkatkan efektivitas pembelajaran bahasa Arab sekaligus memperkuat kompetensi kebahasaan dan komunikatif peserta didik.